Spatial Variance of Soil Available Nutrients in Continuous Cropping of Zea May L. Plantation in Central China - Haisheng Chen, Qiankun Hong, Linsheng Cai, Zhenyu Li, Youcong Zhu (Forest Chemicals Review)
Revealing the spatial variance characteristics of soil available nutrient properties is important in carrying out precise fertilization in Zea may L. plantation. The spatial variance characteristics of soil nutrients contents including total N, available P, and available K were examined on a 87 ha long -term Zea may L. plantation in Jia County of Henan province based on geostatistical techniques, which can help in precise fertilization of the fields. The results indicated that the structure of AP and AK showed moderate spatial dependence, indicating their spatial variance were controlled by intrinsic factors and extrinsic factors, while the structure of TN showed strong spatial dependence, indicating that its spatial variance was mostly determined by intrinsic factors. The contour maps for soil TN, AP, and AK obtained from this study exhibit a rather patchy distribution. Our results provided the basis for precise fertilization of Zea may L. plantation in central Henan province, China.